Stacked Veterinary Cuttable Plates for Treatment of Comminuted Diaphyseal Fractures in Cats - McLaughlin, R. M.; Cockshutt, Joanne R., Jr.; Kuzma, A. B. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
Comminuted long bone fractures in four cats were repaired using stacked 2.0/2.7 mm cuttable plates. The plates were used as “lengthening plates", spanning cortical defects to maintain limb length. The defects were filled with autogenous cancellous bone graft. The plates did not fracture through unfilled screw holes and good to excellent limb function returned in all four cats.
Keywords: Cuttable plate; comminuted fracture